Panoramy w Ameryce - Ławniczak, Grażyna (My University, 1995)
Pierwsza panorama polska "Racławicka" przetrwała w pełnym wymiarze płótna panoramowego 15 x 120 m, udostępniona zwiedzającym od 1985 r. w specjalnie zbudowanej rotundzie we Wrocławiu – jest to oddział Muzeum Narodowego. Panorama "Golgota" druga z polskich panoram, w formacie półpanoramy – hemicykl 15 x 60 m, która zachowała się, jest mało znana dziś – zapomniana, znajduje się na terenie kompleksu Forest Lawn Memorial Park (od 1951 r.) w pobliżu Los Angeles. Tworzenie panoram i ich wystawy, należały do przedsięwzięć komercyjnych nastawionych na zysk. Z czasem wystawy zamykano, a malowidła przekazywano autorom, którzy najczęściej rozcinali panoramę na części i po przemalowaniach sprzedawali, jako samodzielne obrazy. Fragmenty panoram, dzieła malarskie są dziś gromadzone przez muzea. Muzeum Okręgowe w Tarnowie poszukuje części panoramy Jana Styki "Bitwa pod Sybinem", sceny centralnej "Generał Bem na koniu". Obraz znany jedynie ze zdjęcia - listu z Poznania z roku 1930, ofercie sprzedaży trzech fragmentów panoramy skierowanej do Miasta Tarnowa. Odnalezione obrazy, fragmenty tej panoramy prezentowane są na wystawie stałej "Panoramy Siedmiogrodzkiej" w Muzeum Okręgowym w Tarnowie. Obrazy Jana Styki ilustracje do "Quo vadis" w postaci czterech tryptyków, towarzyszyły wystawie panoramy "Męczeństwo Chrześcijan w cyrku Nerona" w Warszawie (1899-1900). Następnie wystawiono je w Paryżu w Gallerie la Boétie, zostały użyte, jako ilustracje powieści Henryka Sienkiewicza "Quo vadis", tłumaczeniu francuskim, w wydawnictwie Ernesta Flamariona w Paryżu 1901 r. Temat "Męczeństwo Chrześcijan" znalazł odzwierciedlenie w powstających wówczas pierwszych obrazach filmowych w wytwórni "Pathé". Obrazy "Quo vadis" znajdowały się w willi Jana Styki w założonym przez niego Muzeum na Capri do 1925 r.

The first Polish panorama, the Racławice Panorama, has survived to our times in its full form of the 15 x 120 meter panoramic canvas and has been made available to the general public in a specially built rotunda structure, a branch of the National Museum in Wrocław, since 1985. The Golgotha Panorama (The Crucifixion Panorama), the second Polish panoramic painting in the form of a semi-panorama, a 15 x 60 meter hemicycle that has been preserved to our times is decidedly less known, in fact almost forgotten, and is currently housed in the Forest Lawn Memorial Park near Los Angeles (since 1951). Creating panoramas and presenting them at exhibitions was a purely commercial enterprise with financial gain in mind. Over time, the exhibitions were closed and the paintings were handed over to their authors who, most frequently, would split the panoramas into separate parts and then, after some adjustments, sell them as individual paintings. Different sections of panoramic paintings are now collected by museums. The Regional Museum in Tarnów, for example, is looking for a part of Jan Styka’s panoramic painting "The Battle of Sybin” (the so-called Transylvania Panorama), i.e. its central part: "Mounted General Bem". The only known image of the painting is the one from the photo included in a letter form Poznań (1930) which was a sale offer of three fragments of the panorama and which was sent to the authorities of the town of Tarnów. The found paintings that once were the component parts of this particular panorama are now on display in a core exposition "The Transylvania Panorama" in the Regional Museum in Tarnów. Jan Styka’s paintings illustrating scenes from "Quo Vadis" in a multiple triptych form were exhibited along with the exposition of the "The martyrdom of the Christians in the circus of Nero" panorama in Warsaw (1899-1900). Subsequently, the panorama was on display in Paris in Gallerie la Boétie, and was then used as the illustrations for Henryk Sienkiewicz’s novel "Quo vadis" in the French translation published by Ernest Flamarion publishing house in Paris in 1901. The subject theme, "The martyrdom of the Christians", found its way into further exploitation in the first silent movies produced by Pathé. Until 1925, the paintings from the cycle "Quo Vadis" were housed in Styka’s private villa in a museum founded by him in Capri.
Keywords: malarstwo polskie; obrazy panoramowe; cineramy; wystawy sztuki i gospodarcze; pamiątki narodowe; Polish paintings; panoramic paintings; cineramas; art and economic exhibitions; national heritage items